Doing legitimacy in talk: the production of leader–follower relationship in spiritual consultation interactions - Chin, Sin Zi; Seng, Hui Zanne; Chan, Mei Yuit (SAGE Publications, 2019)
Spiritual leaders achieve power over their followers through various means. Often overlooked is what happens in the interaction between spiritual leaders and their followers in the creation and legitimation of the leader’s power. In this study, we examined the discursive construction of leader–follower relationship in consultation interactions between a spiritual leader and his followers. Fifteen consultation sessions were analyzed using the discourse analytical approach. The analysis focused on legitimation and discursive strategies used by the leader to legitimize his power over his followers. The findings show that a set of strategies are relied on as standard procedure by the leader to reinforce his authority, used when interacting with a compliant followership. However, a different set of strategies are deployed in situations when the leader’s authority is challenged. The results reveal that the authority of the leader is not a natural given, but needs to be actively negotiated and defended in the ongoing process of interaction.